Primary amnesia of insidious onset with subsequent stabilisation. Issue 11 (November 1994) - Lucchelli, F; De Renzi, E; Perani, D; Fazio, F
Abstract : A patient had a slowly developing amnesic syndrome that remained substantially unchanged during the two and a half years of observation. Intellectual skills were excellent and there was no language, perception, praxis, or calculation deficit. The memory impairment involved verbal and visual learning, sparing spatial learning and, to a large extent, retrograde memory. Magnetic resonance imaging was normal, but PET showed a hypometabolism of the left temporal mesial region and thalamus. This case extends the spectrum of monosymptomatic cognitive disorders, previously reported in the area of language, praxis, and visual recognition, to amnesia.